The Relationship of the Role of Nurses in Health Services with Patient Satisfaction - Subianto; Rahman, Abd; Alam, Muh Syahrul (Omni Health Journal, 2025)
Background: The role of a nurse represents a dynamic function within the healthcare system, encompassing responsibilities, obligations, and expected behaviors aligned with professional status. In public health settings, the role of nurses significantly contributes to the perceived quality of service and patient satisfaction. Objective: This study aims to examine the relationship between the perceived role of nurses and the level of patient satisfaction at the Health Quarantine Post in the Tanjungpandan Work Area. Methods: This research employed a quantitative, observational analytic design with a cross-sectional approach. A total of 30 respondents were selected using non-probability sampling, specifically accidental sampling. Data were collected through a structured patient satisfaction questionnaire and analyzed using descriptive statistics and chi-square tests to determine the association between the variables. Results: Of the 30 respondents, 66.7% were female and 33.3% were male. All participants (100%) rated the role of nurses as “good.” In terms of satisfaction, 97% of respondents reported being “very satisfied,” while 3% were “satisfied.” Statistical analysis using the chi-square test demonstrated a significant relationship between the role of nurses and patient satisfaction (p < 0.05). Conclusion: The findings indicate a strong positive correlation between the nurses’ professional role and patient satisfaction at the health quarantine facility. Services related to clinical examinations, transportation checks, and the issuance of fitness-to-fly documents were delivered effectively, contributing to high satisfaction levels among service users.